Chloroplast symbiosis in a marine ciliate: ecophysiology and the risks and rewards of hosting foreign organelles - Mcmanus, George B.; Schoener, Donald; Haberlandt, Katharine (Frontiers in Microbiology, 2012)
Simultaneous use of both heterotrophic and autotrophic metabolism (“mixotrophy”) is common among protists. Strombidium rassoulzadegani is a planktonic mixotrophic marine ciliate that saves chloroplasts from its algal food and obtains a nutritional subsidy via photosynthesis. Cultures from the northeast, northwest, and southwest Atlantic Ocean show similar numerical response parameters (maximum growth rate, food concentration at which growth is half its maximum, and threshold food concentration for growth), and some isolates have been maintained in vitro for over three years. This ciliate grows equally well when fed on the green alga Tetraselmis chui (strain PLY429) or the cryptophyte Rhodomonas lens (strain RHODO). It appears to be an obligate mixotroph, requiring both food and light to achieve positive growth, when feeding on either of these algae. However, it has also been grown for several weeks (> 10 generations) heterotrophically on the dinoflagellate Prorocentrum minimum (strain EXUV) during which it grows better in dark than in light. In this paper, we review the ecology of S. rassoulzadegani, discuss some aspects of its photo- and feeding physiology, and speculate on benefits and costs to the ciliate of chloroplast symbiosis.